Distance Learning in Teaching Mathematics: Perspective and Challenges of Primary School Teachers - Abri, Samah; Hamadi, Asma; Mazroui, Maryam; Sadi, Maryam; Tashtoush, Mohammad (Information Technology and Science (ITScience), 2023)
This study aimed to identify the practices and challenges faced by primary school female teachers when implementing the distance learning strategy in teaching mathematics, based on two variables: number of years of service and the number of technical training courses and programs. The study sample consisted of (47) teachers from the primary school female teachers. A validated and reliable questionnaire was administered. The results showed that there are some challenges facing teachers when implementing the distance learning strategy, such as increased workload and tasks, weak and intermittent internet connectivity, and the need for greater effort compared to traditional teaching methods. The results also showed that teachers who have received a higher number of technical training courses and have fewer years of service face fewer challenges compared to newly appointed teachers who have not undergone an adequate number of technical training courses.